Aerobowa termofilowa biodegradacja materii organicznej - Graczyk, Magdalena; Kołaczkowski, Stanisław T. (Zielona Góra: Uniwersytet Zielonogórski)
The aerobic thermophilic method of biodegradation of organic wastes is well known and used sinee very long, but precision is wanting in the knowledge of the course of this process. A reviev of bibliography made in this paper, indicate the possibility of a large employment of this well regulated process, to render harmless the organic matter ot sludge and high concentrated wastewater.
Keywords: materia organiczna; biodegradacja